Motivasi Berwirausaha Generasi Millenial Berbasis Kuliner Di Kelurahan Maccorawalie Kecamatan Watang Sawitto Kabupaten Pinrang - Risma, Risma; Irmayani, Irmayani; Sriwahyuningsih, A Erna (LaGeografia, 2021)
This study aims to determine the motivation of the culinary based millenial generation entrepreneurship in Maccorawalie Village Watang sawitto Disrict, Pinrang Regency. This research was conducted from August to October.The data collection method used was observation, questionnaires and interviews. And dataÂ  sources usedare primary data and seconddary dataa. Data analysis use in this research is descriptive statistics using the Likert scale method with a measurement scale that is Very high (5), High (4), Medium (3), Low (2), Very Low (1).The results of this study indicate that there are 4 Sub variables namely income, freedom/comfort, Personal dreams, independence that motivates culinary based millenial generation entrepreneurship in Maccorawalie Village, Watang Sawitto sub-district, Pinrang district.And of the 4 Sub Variables that most motivate entrepreneurship is the income sub variables with a value of 535 belonging to the very high category.